Effect of electroporation on microbial cell wall to extract lipid - Umi Rabiatul Ramzilah, P. Remli (2017)
Nowadays, fossil fuels are still the primary energy sources but it cannot hold for a lifetime. Therefore, to overcome this limitation, biofuel is considered as a sustainable solution. A number of methods have been developed for producing biodiesel but with traditional method its take more time and associated with usage of huge amount of toxic solvents. Therefore, our research aimed how to produce biodiesel in a short time, with less energy input and eco-friendly. To do this we used electroporation process, where we employed a high voltage for shorter time on yeast cell to disrupt them. Our reactor took around 10 minutes to disrupt the cell wall for escaping intracellular lipid which could be used for biodiesel synthesis. Then, from the electroporation, we can extract and quantify the lipids for further applications. Lipid extraction and quantification is the accurate and faster method to determine the lipid content that involve cell wall breakup and extraction with organic solvent. In lipid quantification, the result shown that, lipid produced is higher when treated with high pulse electric field at 10 minutes with 2 cm distance. This is due to the lower distance between the electrodes that influenced the intensity of the voltage applied to the treatment media. Furthermore, the longer the treatment time, more microbial cell wall was disrupt causing more intracellular lipids to come out to the surface. Finally, the potential of biofuels as one of energy source cannot be overlooked from the result of the present research because they can contribute considerably to supply energy for future.